Political communication online structures, functions, and challenges - Seizov, Ognyan (Routledge research in political communication, 2014)
[This book] places these developments in their social and media context, covers various disciplinary backgrounds and how they can contribute to a common understanding of the evolving online media landscape, and proposes a novel methodological tool for the analysis of political communication online. Seizov offers an approach that places context at the core of the theoretical and methodological discussion by discussing the traits of online communication that make it a unique communication environment. The book then brings together different disciplines which have important contributions for the study of political communication online but have not been integrated for this purpose so far, such as visual communication, multimodal research, and cognitive psychology. Seizov introduces the book's main theoretical and methodological contribution to multimodal document analysis, the annotation scheme "Imagery and Communication in Online Narratives" (ICON), and explores how the ICON approach works in practice. Taking four distinct genres of online political communication - news, election campaigns, NGOs, and social movements - the book presents the analyses of convenience samples from each of them in detail.